EFEKTIFITAS MODEL PEMBELAJARAN DIRRECT INSTRUCTION DENGAN STRATEGI MOTIVASI ARCS PADA MATERI GRAPH - Kuswardi, Yemi; Kurniawati, Ira; Sutopo, Sutopo (Journal of Mathematics and Mathematics Education, 2011)
ABSTRACT Graph  materials  contains  declarative  knowledge  and  procedural knowledge.  In  Graph  subject  included declarative  knowledge  is  the  graph  terminology  while  those  included  procedural  knowledge  is  how  to determine  the  settlement  of  problems  by  using  the  algorithm  methods  associated  with  Graph.  Dirrect instruction  that  relies  on  principles  of  behavioral  and  social  learning  theory,  has  been  specifically designed to support students learning processes associated with procedural knowledge and declarative knowledge is well structured and can be taught with the pattern of activity that gradually, step by step. ARSC  motivation  strategies  (Attention,  Relevance,  Confidence,  Satisfaction)  is  a  strategy  that  can increase  the  motivation  on  learning  materials  and  learning  activities  of  students.  Application  of  direct instruction model with ARCS motivational strategies is one solution to resolve the issue. The purpose of this  study  was  to  determine  whether  the  aplication  of  direct  istruction  model  using  ARCS  strategy  on graph materials subject (1) the mastery learning is achieved, (2) students learning activities are effective, (3)  students  responses  are  positive,  and  (4)  the  effectiveness  of  model  is  reached.  This  research  is  a qualitative  descriptive  research.  The  subjects  of  this  research  are  students  who  take  Discrete Mathematics course in Educational Mathematics Program, Department of Educational Mathematics and Science,  FKIP,  Sebelas  Maret  University  Surakarta.  The  results  is  (1)  mastery  learning  achieved,  (2) learning  activities  are  effective,  (3)  students  response  considered  positive,  (4)  the  effectiveness  of interactive learning on graph is achieved. Keywords: Dirrect Instruction Model, Motivation Strategies ARCS, Discrete Mathematics, Graph